The correlation between creatinine levels and estimated glomerular filtration rate (GFR) with blood glucose levels in diabetes mellitus type 2 patients - Ani Riyani; Rizka Nerisandi; Wiwin Wiryanti; Widda Rahmah; Nani Kurnaeni (PAGEPress Publications, 2023)
Diabetes mellitus (DM) was a group of metabolic diseases characterized by hyperglycemia. Measuring the blood creatinine level and calculating the estimated glomerular filtration rate (GFR) was crucial in determining if a person had impaired kidney function. These tests provided valuable insights into the progression of type 2 diabetes mellitus and its associated risk of kidney failure. The objective of this study was to investigate the correlation between average creatinine levels and GFR with blood glucose levels in type 2 DM patients. This correlative research used a cross-sectional approach and included samples from 30 patients with type 2 DM at a hospital in Bandung, Indonesia. The patients' blood glucose and blood creatinine levels were measured using GFR calculations and a Kenza Max photometer, respectively. The sampling method used was accidental sampling, with the sample criteria being type 2 DM patients who were willing to be respondents and did not have hypertension. The average creatinine levels and estimated GFR values were 0.97 mg/dL and 84.971 mL/min/1.73m². The results of the Pearson correlation test indicated non-significant correlations (p > 0.05, p = 0.703 and 0.819). This suggested that there was no significant relationship between creatinine levels and estimated GFR and blood glucose levels in type 2 DM patients. This study provided a foundational exploration of the link between blood glucose levels and kidney function, which could contribute to developing methods for examining kidney diseases in type 2 DM patients. This study's findings underscore the complexity of the relationship between metabolic control and renal function in type 2 diabetes mellitus patients, highlighting the need for individualized patient assessment and management strategies.